Design optimization of the interior vehicle noise and vibration through computational approaches - Al-Dhahebi, Adel Mohammed Mohammed (Institute of Engineering Mathematics, Universiti Malaysia Perlis, 2017)
The specific objectives of this study are ; to develop acoustical comfort index calledNoise Isolation Index (NII) to evaluate the acoustical comfort in the vehicle cabin by considering the psychoacoustics measures of the exterior and interior sounds ; to cluster noise and vibration using K-mean clustering algorithm in order to compare the interior comfort level of Axia, Myvi and Viva on stationary (idle), non-stationary (highway, pavement and urban) driving conditions ; to develop Genetic Algorithm (GA) model to obtain the comfort level in the interior vehicle cabin. GA aims to search for the promising loudness and vibration values which produce minimum noise in the interior vehicle cabin.